Physiological adjustment effect of visual stimulation by fresh rose flowers on sympathetic nervous activity - Ikei, Harumi; Song, Chorong; Miyazaki, Yoshifumi (Frontiers in Psychology, 2023)
As modern societies are often stressful due to urbanization and artificialization, the physiological relaxing effects of natural environments or nature-derived stimuli on humans have attracted attention and scientific data are being accumulated. It is known that there is inter-individual variation in these effects. The study aim was to apply the law of initial values to investigate the physiological adjustment effect of viewing fresh roses on sympathetic nervous activity. In this crossover study, a total of 214 high school students, office workers, healthcare workers, and elderly people were analyzed. The participants viewed fresh roses in a vase for 4 minutes. In the control condition, participants did not view any fresh roses during the period. To offset any order effect, participants received visual stimuli in the order of fresh roses then the control (no fresh roses) or the control and then fresh roses. ln (LF/HF) of heart rate variability (HRV) obtained from aa interval measurements using an acceleration plethysmograph and used as an index of sympathetic nervous activity. The initial value was ln(LF/HF) of HRV during the control viewing (no fresh roses), and the change value was ln(LF/HF) of HRV during visual stimulation by fresh roses minus the control viewing. The correlation between the two was assessed by determining Pearson’s correlation coefficient r, which was significantly negative. A physiological adjustment effect was observed such that participants with high initial sympathetic nervous activity showed a decrease in activity after visual stimulation with fresh roses, whereas participants with low initial activity showed an increase.